การศึกษาความพึงพอใจในการปฏิบัติงานของครูโรงเรียนเอกชนระดับประถมศึกษา เขตการศึกษา 6 - ไตรธร เศรษฐีธร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this research is to study the level of performance satisfaction of the private elementary teachers in the educational region 6. It is done in accordance with the motivation-hygiene theory or the two-factor theory, which belongs to Federick Herzberg. The subjects of this research are therefore the private elementary teachers of this area. The researcher had distributed 310 copies of questionnaires to them. The respondents were 285 copies or 91.93%. The SPSS/PC+ program was used to calculate percentage, means, and standard deviation of the data. The research result was found that the private elementary school teachers had high satisfactory level with their jobs. Most of them ranked their satisfactory level very high which can be shown in a descend order as follows: supervision, job security, responsibility, progression, relationships iwth colleague, relationships with boss, private life, policy and management, job characteristics, and atmosphere. Other factors were ranked at satisfactionlevel, which are job accomplishment, self-esteem, salary, and fringe benefits. When considering the overall aspect, the research finds that the private elementary teachers had high degree of performance satisfaction.